Estimates of genetic and phenotypic parameters for plant and seed characteristics in an opaque maize population - Tosello, Geraldo A.; Souza Jr., Claudio L.; Geraldi, Isaias O. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
A single population with a broading genetic variability having an opaque kernel phenotype was used in this study in order to estimate genetic parameters associated with yielding, plant and ear height, %protein, % tryptophan and % tryptophan in the protein. A total of 364 half-sib progenies were evaluated using a lattice square design with two replications. The additive genetic variances found for yielding (σ2A = 333.44 g/pl), plant height (σ2A = 187.85) and ear height (Σ2A = 122,08) indicated that there are enough genetic variability among progenies. For those characteristics associated with protein quality the genetic additive variance detected among progenies are showing that genetic progress with selection can be achieved within those characters. Estimates of genetic correlations between yielding and plant or ear height had a low value suggesting that if one select for yielding, the plant and ear height will not be affected. The genetic correlation between yielding and protein quality was positive for % protein (rA = 0.303), negative for % tryptophan (rA = -0,178) and negative for % tryptophan in the protein (rA = -0,568). It was also found a negative genetic correlation for % protein and % tryptophan in the protein (rA = -0,591). The data in this stud has been shown that if one select for yielding ability the protein quality will decay, but because of the enough genetic variability present in the population it will be possible to select for quality without changing the yielding.